Loss factor and impedance analysis for the diamond storage ring - Bartolini, R; Fielder, R; Thomas, C (2013)
Diamond Light Source is investigating the possibility of increasing the storage ring operating current above the nominal 300 mA. A campaign of measurements and simulations has been carried out in order to understand the extent of the parasitic energy loss and characterise the most important items which build up the machine impedance. In this paper we report on the most recent measurements of the longitudinal loss factor and the present status of the impedance database with an initial comparison between the two. Copyright © 2013 by JACoW.